Narrativas Sobre La Experiencia Profesional De Tres Psicologas En Torno A La Danza Movimiento Terapia (2017)
In this study we describe the narratives of three Psychology professionals with studies and experience surrounding the Dance Movement Therapy with psychotherapeutic use in emotional expression, in nonverbal communication. The research was carried out with three Psychology professionals, being a research of qualitative type with narrative design. Among the main results we can mention that from the professional experience D.M.T is evidenced as an alternative psychotherapeutic approach that promotes the physical and mental integration of the individual. Of the main conclusions can be said that it is applicable to population diversity with different diagnoses, dysfunctions and victims of violence, it is also positioned as a therapeutic alternative to the traditional one carried out through the word, since it uses the moving body as a means therapeutic, offering therapeutic alternatives those people who have difficulty expressing verbally.